État des lieux des ictères néonatals au niveau du service de néonatologie de l’E.H.S mère-enfant Docteur Saadane Laghouat durant la période du 01 Janvier 2019 au 31 Décembre 2019 - Bensaad Sirine Nour Elhouda; Rahmani Hiba (Université Amar Telidji de Laghouat Faculté de Médecine, 2021)
Jaundice is a very common pathology during the neonatal period since more than 50% of term newborns present with transient and benign hyperbilirubinimia associated with hepatic immaturity. However, pathological jaundice accounts for 5 to 10% of neonatal jaundice, it can be serious when it is unconjugated bilirubin and causes neurosensory squeal, the most serious form of which is kernicterus. In contrast, neonatal cholestasis is due to conjugated bilirubin and it is not neurotoxic, but their delayed diagnosis poses real etiological problems delaying adequate management, all of which has the consequence of worsening the prognosis of these children. This work concerns a retrospective study of 125 newborns with jaundice, hospitalized in the E.H.S Neonatal Department Doctor Saadane LAGHOUAT during the period of one year 2019. A slight female predominance was recorded with 52.8%, consanguinity was revealed in 11 jaundiced newborns. 8.8%, almost half of the cases in our population had presented with precose jaundice and 79.2% of these newborns had severe jaundice on admission. 19.2% of jaundiced newborns presented signs associated with their jaundice: signs of hemolysis - signs of cholestasis - signs of infection) and 7.9% had a disturbed neurological examination. The aetiologies are dominated by ABO incompatibility 41%, physiological jaundice 34%, post-infectious 7.2% and cholestatic jaundice 3.2%. In our series of studies, treatment is mainly based on phototherapy in combination with other treatments:albumin in 32 % and Intravenous polyvalent immunoglobulin in 15 %. 02 newborns benefited from the exsanguino-transfusion. The short-term course is favorable in 93.6% of newborns and 3.2% discharged with neurological sequelae. And mortality was recorded in 2.4% of cases. In the neonatology department EHS Doctor SAADANE LAGHOUAT, jaundice is one of the most frequent reasons for hospitalization from which our study was carried out because there are still cases of severe jaundice complicated by kernicterus and cholestatic jaundice. Who came out without a precise etiological diagnosis?
126 p.